Mobile Smartphone in Foreign Language Teaching: Apps for Teaching Students’ Vocabulary - Razaq, Yusuf; Idman, Muhajirah; Khair, Ummul; Firmah, Andi (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This study focuses on determining whether or not students at MTs As'adiyah Putra 1 Sengkang's first year can expand their vocabulary through the use of mobile smartphones. The pre-experimental design was used by the researcher. First-year students at MTs As'adiyah Putra 1 Sengkang during the academic year 2020–2021 made up the population of this study. The class of 34 students served as the sample for the purposive sampling technique. The pretest and posttest were used to collect the data. The results of the student's test scores were determined by utilizing SPSS 24 to evaluate the test's data. According to the researcher's findings, the pre-test mean score was bad (49.00), but the post-test mean score was extremely high (79.24), with a standard deviation of 15.47 and 10.95, respectively. Therefore, the researcher came to the conclusion that employing a mobile smartphone was efficient for increasing vocabulary in first-year MTs Putra 1 As'adiyah Sengkang.